Optical Imaging of Apoptosis as a Biomarker of Tumor Response to Chemotherapy - Schellenberger, Eyk A (Neoplasia Press Inc., 2003)
A rapid and accurate assessment of the antitumor efficacy of new therapeutic drugs could speed up drug discovery and improve clinical decision making. Based on the hypothesis that most effective antitumor agents induce apoptosis, we developed a near-infrared fluorescent (NIRF) annexin V to be used for optical sensing of tumor environments. To demonstrate probe specificity, we developed both an active (i.e., apoptosisrecognizing) and an inactive form of annexin V with very similar properties (to account for nonspecific tumor accumulation), and tested the agents in nude mice each bearing a cyclophosphamide (CPA) chemosensitive (LLC) and a chemoresistant LLC (CR-LLC). After injection with active annexin V, the tumor-annexin V ratio (TAR; tumor NIRF/background NIRF) for untreated mice was 1.22 ± 0.34 for LLC and 1.43 ± 0.53 for CR-LLC (n = 4). The LLC of CPA-treated mice had significant elevations of TAR (2.56 ± 0.29, P = .001, n = 4), but only a moderate increase was obtained for the CR-LLC (TAR = 1.89 ± 0.19, P = .183). The in vivo measurements correlated well with terminal deoxyribosyl transferasemediated dUTP nick end labeling indexes. When inactive Cy-annexin V was used, with or without CPA treatment and in both CCL and CR-CCL tumors, tumor NIRF values ranged from 0.91 to 1.17 (i.e., tumor were equal to background). We conclude that active Cy-annexin V and surface reflectance fluorescence imaging provide a nonradioactive, semiquantitative method of determining chemosensitivity in LLC xenografts. The method maybe used to image pharmacologic responses in other animal models and, potentially, may permit the clinical imaging of apoptosis with noninvasive or minimally invasive instrumentation.